If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3) + 2(5) = 60x + -500 Multiply 3 * 3 9 + 2(5) = 60x + -500 Multiply 2 * 5 9 + 10 = 60x + -500 Combine like terms: 9 + 10 = 19 19 = 60x + -500 Reorder the terms: 19 = -500 + 60x Solving 19 = -500 + 60x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60x' to each side of the equation. 19 + -60x = -500 + 60x + -60x Combine like terms: 60x + -60x = 0 19 + -60x = -500 + 0 19 + -60x = -500 Add '-19' to each side of the equation. 19 + -19 + -60x = -500 + -19 Combine like terms: 19 + -19 = 0 0 + -60x = -500 + -19 -60x = -500 + -19 Combine like terms: -500 + -19 = -519 -60x = -519 Divide each side by '-60'. x = 8.65 Simplifying x = 8.65
| 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 | | (p/2)/2 | | 3+3=8x+23 | | (x)(x)-11x+18=0 | | 3/2y-8=-5 | | 7x+20=3x+36 | | 2x+9=2x+3 | | x^2=5y+35 | | 4+3x=6x-83x-12 | | -3x+5(-6x+4)-(-30x+16)=-9(x-5) |